New data on buried archaeological ruins in Messina area (Sicily-Italy) from a ground penetrating radar survey. (February 2018) - Imposa, S.; Grassi, S.; Patti, G.; Boso, D.
Abstract: A ground penetrating radar survey was performed in a small area located near the Messina harbor, northeast Sicily, with the aim of discovering the presence of archaeological remains. Numerous findings, dating from the seventh and sixth centuries B.C., have been discovered in the neighboring areas over recent years. A survey grid of longitudinal and transverse scans, covering an area of about 400 m 2, was designed. Two-dimensional radar sections (distance – depth) have been obtained from data processing. The reflections observed are often "isolated", as though caused by fairly small objects or artifacts. Only through the comparative analysis between adjacent scans a lateral continuity of the reflections could be observed, thus allowing the correlation with possible remnants of walls. The depth-slices, obtained by further processing, have allowed observing how the signal changes are distributed both in depth and laterally, showing numerous reflections, located between 0.30 and 1.10 m depth. This survey revealed the presence of several possible archaeological remains. By correlating the data obtained from the GPR survey with the archaeological knowledge on the discoveries made in the surrounding areas, it was possible to interpret the linear reflectors as wall remains, probably dating back to the Hellenistic period. Highlights: Georadar is a method with useful applications in the archaeological field. A GPR survey was performed to identify archaeological ruins in the subsoil of the Messina area. Radargrams and depth-slices were obtained by the data elaboration. The survey has highlighted buried ruins of likely Hellenistic age. GPR proved to be an efficient tool for detecting buried archaeological ruins.